Advancing the federal research agenda on violence against women - Kruttschnitt, Candace; McLaughlin, Brenda L.; Petrie, Carol (National Academies Press, 2004)
Based on the presentations and deliberations of a workshop convened by the National Research Council in January 2002 to develop a detailed research agenda on violence against women, this report addresses the nature and scope of violence against women, social ecological risks of violence against women, prevention and deterrence, identifying and treating offenders, and the future of research on violence against women. This report expands on the work of an earlier National Research Council panel whose report, "Understanding Violence Against Women," was published in 1996. Although some of the research recommended in that report has been funded and performed, important gaps in research remain. The current report presents the conclusions and recommendations of the workshop as subsequently framed by the steering committee. Regarding the research focus, the steering committee questions whether the general origins and behavioral patterns of the various forms of violence are sufficiently different to warrant the degree of separation that has occurred. The committee believes some level of integration of research on violence against and by women with the larger literature on crime and violence would enrich the former research intellectually, increase the amount of attention it receives, extend the lessons that can be learned about violence against women, and provide a more solid basis for prevention and deterrence strategies. The committee further believes that the research agenda of the Federal Government regarding violence against women would benefit from integration with efforts to determine the causes, consequences, prevention, treatment, and deterrence of violence more broadly. Regarding the prevalence of violence against women, the committee recommends a more coordinated research strategy to help improve prevalence data. Regarding research on the causes of violence against women, the committee recommends that work be initiated to examine the feasibility and cost-effectiveness of conducting longitudinal studies on violence against and by women. The committee also recommends event-based studies that would address the situational contexts and dynamic interactions that lead to violence against women, with attention to research on the processes that underlie victim selection, location selection, and victim-offender interaction patterns. Recommendations on social ecological studies pertain to the social and spatial epidemiology of violence, the distribution of services, the social area effects on sanctions and services, and data needs. Research recommendations are offered on prevention and treatment, as well as deterrence